Real Estate Accounting Made Easy, 2nd Edition - Ebisike, Obioma (Wiley, 2019)
Grasp the fundamentals of real estate accounting, finance, and investments Real Estate Accounting Made Easy is just that-an accessible beginner's guide for anyone who needs to get up to speed on the field of real estate accounting, finance, and investments. Beginning with the elementary aspects of real estate to ensure that you're comfortable with the subject matter, it goes on to explore more in-depth topics in a way that's easy to digest. The book begins with discussions on introduction to the real estate industry and basic real estate accounting. Building on knowledge from the initial chapters, the book goes on to cover the different form of real estate organizations, financial statements such as the balance sheet, income statement, shareholders equity and the statement cash flow, and more. • Provides theories and practices of real estate from an accounting, financial, and investments perspective • Advanced transactions are discussed in an easy-to-understand manner • Content reflects the FASB's new standards on revenue recognition and lease accounting • Accounting for operating property expenses, operating expenses reconciliation and recoveries, lease incentives and tenant improvements, budgeting, variance analysis are discussed in detail • Covers types of financing for real estate acquisitions, accounting for real estate investments, project development costs, and real estate brokerage • The book also walks you through the financial audit process If real estate is a new territory for you, fear not! This book helps new auditors, accounting, finance, and investment professionals, and users of financial reports understand the fundamentals of the financial aspect of the real estate business.